The Flypaper Effect Phenomenon: Evidence from Indonesia (European Journal of Formal Sciences and Engineering, 2023)
One of the implementations of autonomy policy is fiscal decentralization. The State gives chance to every local government for improving its fiscal ability. Original Local Government Revenue (PAD) is fiscal potency owned local government to improve local government independence to promote welfare to society. To accelerate fiscal independence of local government equally, the central government sends transfer funds in the form of General Allocation Funds (DAU) which aims to comply local government expenditure that has not fulfilled. However, problems faced is local government expenditure management still much more affected by DAU rather than PAD. It indicates that local government still depends on central government to comply expenditure called flypaper effect. This research aims to analyze the effect of PAD and DAU on local government expenditure by identifying whether occurs flypaper on provincial government in Indonesia. The method used in this research is analysis regression of panel data with Generalized Least Square (GLS). Data used is panel data from 34 provinces in Indonesia between 2008-2017. Based on results estimation, PAD and DAU positively and significantly affect local government expenditure. However, the DAU more affects local government expenditure compared with PAD. This exhibits that flypaper effect phenomenon occurred on provincial government in Indonesia which local government expenditure response more affected by DAU than PAD. It is happening due to the provincial government still relies on central government to comply its expenditure illustrated with high DAU transfers. This research concludes that decentralization policy in Indonesia is not effective yet. Thus, the government needs to adjust decentralization policy in order to improve regional fiscal independence.
Keywords: Original Local Government Revenue (PAD), General Allocation Fund (DAU), Local Government Expenditure, and Flypaper Effect.